Efficacy and safety of mesenchymal stem cells treatment for multidrug-resistant graft-versus-host disease after haploidentical allogeneic hematopoietic stem cell transplantation. (January 2022) - Shen, Meng-Zhu; Liu, Xin-Xin; Qiu, Zhi-Yuan; Xu, Lan-Ping; Zhang, Xiao-Hui; Wang, Yu; Yan, Chen-Hua; Chen, Huan; Chen, Yu-Hong; Han, Wei; Wang, Feng-Rong; Wang, Jing-Zhi; et al.
Purpose: Graft- versus -host disease (GVHD) is an important complication after human leukocyte antigen (HLA) haploidentical donor (HID) hematopoietic stem cell transplantation (HSCT), which may lead to poor prognosis. Our study intends to identify the efficacy and safety of mesenchymal stem cells (MSCs) for multidrug-resistant (MDR)-GVHD after HID HSCT. Methods: MDR-GVHD was referring to GVHD remaining no response to at least two types of therapy, and hUCB-MSCs were given at the dose of (1.0–2.0) × 10 6 /kg once a week. Results: A total of 21 patients were enrolled in this retrospective study (acute GVHD (aGVHD): n  = 14, chronic GVHD (cGVHD): n = 7). The median dose of MSCs was 1.2 × 10 6 cells/kg (range, 0.8–1.8 × 10 6 ) cells/kg, and the median numbers of infusion were 2 (range, 1–7) and 3 (range, 2–12) for MDR-aGVHD and MDR-cGVHD patients, respectively. In MDR-aGVHD patients, the overall response rate (ORR) was 57.1%, including 50.0% complete response (CR) and 7.1% partial response (PR), and the median time to response was 49.5 days (range, 16–118) days. The 2-year probability of overall survival after MSCs was 64.3%. Five patients (35.7%) developed infections after MSCs, and no obvious hematologic toxicities were observed. Five MDR-aGVHD patients died after MSCs treatments because of GVHD progression ( n  = 1), severe infection (bacterial central nervous system infection: n  = 1; fungal pneumonia: n  = 2), and poor graft function ( n  = 1). In MDR-cGVHD patients, three patients (42.9%) achieved PR after MSCs and the median time to response was 56 days (22–84) days. The ORRs for moderate and severe cGVHD were 50.0% and 33.3%, respectively. Four MDR-cGVHD patients died after MSCs treatments because of GVHD progression ( n  = 2), severe fungal pneumonia ( n  = 1), and relapse ( n  = 1). Conclusion: MSCs treatment may be safe and effective for MDR-GVHD after HID HSCT.